2014
DOI: 10.14744/nci.2014.30074
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with outpatient health care services: evaluation of the components of this service using regression analysis

Abstract: OBJECTIVE:In health care services, patient’s expectations, and satisfaction levels are important markers of the services provided. The aim of this study is to determine patient satisfaction level, and its influential factors in patients receiving treatment on an ambulatory basis who applied to a state hospital.METHODS:In this cross-sectional study a total of 210 patients were face-to-face interviewed, and patient satisfaction questionnaire survey was performed. Socioeconomic characteristics, physical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…General communication skills have been found to be the main factor explaining a positive assessment of hospitals, 35 but individual differences among physicians and nursing staff in terms of communication competency have not been studied extensively, since most studies rely on aggregate institutional scores. Moreover, within staff, comparisons are usually performed through pre-experimental designs in which a group exposed to a communication enhancement intervention is compared to a control group.…”
mentioning
confidence: 99%
“…General communication skills have been found to be the main factor explaining a positive assessment of hospitals, 35 but individual differences among physicians and nursing staff in terms of communication competency have not been studied extensively, since most studies rely on aggregate institutional scores. Moreover, within staff, comparisons are usually performed through pre-experimental designs in which a group exposed to a communication enhancement intervention is compared to a control group.…”
mentioning
confidence: 99%
“…2.1.3 Outpatient clinic characteristics. Vural et al (2014) have studied patient satisfaction with outpatient health care services. Results showed that nearly all patients namely customers favorably evaluated health care services provided which was found to be related to many factors.…”
Section: Nutritionmentioning
confidence: 99%
“…In Turkey as well patient satisfaction is pilar of the quality of care provided to the patient; according to Vural et al, in 2014 as shed light on communication skills for all healthcare professionals to improve patient satisfaction [11].…”
Section: Introductionmentioning
confidence: 99%